If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 11 = -1x + 1 Reorder the terms: 11 + 9x = -1x + 1 Reorder the terms: 11 + 9x = 1 + -1x Solving 11 + 9x = 1 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 11 + 9x + x = 1 + -1x + x Combine like terms: 9x + x = 10x 11 + 10x = 1 + -1x + x Combine like terms: -1x + x = 0 11 + 10x = 1 + 0 11 + 10x = 1 Add '-11' to each side of the equation. 11 + -11 + 10x = 1 + -11 Combine like terms: 11 + -11 = 0 0 + 10x = 1 + -11 10x = 1 + -11 Combine like terms: 1 + -11 = -10 10x = -10 Divide each side by '10'. x = -1 Simplifying x = -1
| 2x+6=-x+3 | | 4x+3=7x+6 | | 8x+11=5x+6 | | X^2+26x=23 | | 5x+8=9x+4 | | 8x^2+5x+h=0 | | 3x+5=28 | | X^2+26x=33 | | 10b-30=7b+6 | | x^2=x^2-12x+61 | | 10x-7=11x+1 | | 10x-14=106 | | -3x^2-7x=-10 | | 4x+6=-30-8x | | 7x^2=2x^2+9 | | 3+6z=13 | | -7x+4=-x-8+5(3-2x) | | 606=2(15)+7(X) | | X+3x=32 | | (x+x+3)3=36 | | x^2-6x=31 | | 19.70=x+(x-8)(1.5)(.65) | | 5x=12-2x^2 | | -(-10a+7n-3)= | | (2+x)2=(8+3)3 | | 13-4x=21-2x | | -3(5X^2+2X+9)+(2x-3)= | | (B^2+7B-2)-(2b^2+2b)= | | 7x^2=-42x | | 4(-6m)(-2)= | | 5-8x=23-2x | | (3+6+5)5=y^2 |